Ijara Ending with Ownership (Lease) A Case Study of Jordanian Islamic Banks - Munir, Al-Hakim; Hanna, Issa, Mohannad; Sameer, Issa, Suzan; Samer, Zakarneh,; Mohammad, Alfalah, Banan (Journal of Ecohumanism, 2024)
The study aims to analyze a comparative analysis of the pricing of the Ijara (Lease) product ending with ownership in four Islamic banks operating in Jordan, namely: Jordan Islamic Bank, Safwa Islamic Bank, Islamic International Arab Bank, and Al Rajhi Bank, where the data was collected through personal interviews with a sample of facilities staff in the four banks who have experience in dealing with the Ijara product ending with ownership, and the data was analyzed using (Excel) For each bank, the rate of return on Ijara, the stability of the return, the amount of mutual insurance, the administrative fees, the grant commission, the internal rate of return (IRR), the possibility of early repayment with deduction from the remaining returns, and the pros, cons and common factors between the four banks were compared. The study found that the Ijara product ending with ownership in Jordanian Islamic banks varies greatly in terms of terms and advantages, and although there are some positives, there is a need for more uniformity and transparency in the provision of this product, and the study recommended that customers should carefully compare different offers before choosing the right bank, negotiate with banks for better terms, and the need to be familiar with the terms of the contract before signing, and develop a financial plan Studied before requesting financing, while ensuring the ability to pay installments regularly, and recommended banks to diversify banking products and apply the fourth form of transfer of ownership (gradual lease contract) because it achieves justice for the parties to the contract and is free from Deception (Gharar) against the tenant.